Improved Binaural Hearing Effects and Sound Source Localization in Listeners with Simulated Unilateral Conductive Hearing Loss: Effect of a Bone Conduction Device - Yu, Chongxian; Wang, Wenqian; Jiang, Yuan; Zhang, Xiaoming; Liu, Yanyan; Wang, Ping; Ni, Xin; Zhong, Mei; Liu, Yujie; Liu, Yehai (Ear, nose, & throat journal, 2024)
Objectives: It has been proven that patients with unilateral conductive hearing loss (UCHL) may encounter typical problems associated with asymmetric hearing, especially in challenging listening environments. In this study, we aimed to determine how UCHL affects speech recognition under multisource competing environments and the ability of sound source localization, as well as whether assistance with a bone conduction device (BCD) can confer hearing benefits in such listening tasks. Design: Acquired UCHL was simulated using an earplug combined with an earmuff in 10 listeners (mean age: 29.9 ± 4.77 years) with bilateral normal hearing (NH), and a within-subject repeated-measures design was used to compare hearing results among three listening conditions: NH (both ears open, C1), unilateral plug (UP) (simulated UCHL, C2), and UP + BCD (simulated UCHL aided with a BCD, C3). The speech reception threshold (SRT) of summation, squelch, and head shadow (HS) effects and the mean absolute error of sound source localization were used as markers for binaural hearing abilities. Results: BCD assistance (C3) improved the summation and HS effects in all listeners with simulated UCHL, resulting in a lower (i.e., better) SRT than that observed in C2; however, no significant differences in squelch effects were observed between C2 and C3. Notably, most listeners exhibited more accurate sound source localization in C3 than in C2. Further, BCD assistance mainly improved localization accuracy when the noise stimuli were presented at low intensities and on the hearing-impaired (plugged) side, suggesting that the benefits of BCD for sound localization are not based on the reacquisition of binaural processing. Conclusions: The current results have clinical implications for the promotion of BCDs in patients with UCHL, especially those with acquired UCHL who are unable to undergo surgery.